2018
DOI: 10.1111/anu.12802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin E level on growth performance, feed utilization, antioxidant capacity and nonspecific immunity of largemouth bass,Micropterus salmoides

Abstract: An 8‐week feeding trial was conducted to explore the optimal dietary vitamin E requirement of largemouth bass. The fish (7.54 ± 0.04 g) were fed diets containing grade level of vitamin E, 14.24 (the basal diet), 79.53, 118.70, 176.32 and 225.32 mg/kg diet, to apparent satiation twice daily. Results showed that the supplementation of vitamin E significantly enhanced the specific growth rate, which may be related to the elevated feed intake, feed efficiency ratio and protein efficiency ratio. The increase of die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 57 publications
1
23
1
Order By: Relevance
“…Previous studies have revealed the role of vitamin E in regulating the stress response in fish (Belo et al, ; Montero et al, ; Trenzado et al, ). Moreover, the beneficial role of vitamin E on growth and feed utilization of fish has been reported (Li et al, ; Liu et al, ; Suárez et al, ; Trenzado et al, ). In the present study, final weight, WG and feed intake were significantly higher in fish fed diets supplemented with vitamin E (Vit E and Combination groups) as compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have revealed the role of vitamin E in regulating the stress response in fish (Belo et al, ; Montero et al, ; Trenzado et al, ). Moreover, the beneficial role of vitamin E on growth and feed utilization of fish has been reported (Li et al, ; Liu et al, ; Suárez et al, ; Trenzado et al, ). In the present study, final weight, WG and feed intake were significantly higher in fish fed diets supplemented with vitamin E (Vit E and Combination groups) as compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The diet of the Vitamin E group was supplemented with an additional 500 mg vitamin E (DL‐α‐tocopherol acetate; Sigma Chemicals) per kg diet. The supplemental levels of vitamin E were selected based on the earlier studies that high levels of vitamin E may improve immunity and stress resistance in fish (Chen et al, ; Li et al, , ; Liu et al, ; Montero et al, ; Niu et al, ; Ortuño et al, ). The Combination (Nano Se plus vitamin E) diet was supplemented with 1 mg Nano Se and 500 mg vitamin E per kg diet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, vitamin E plays an important role in modulation of immune response, such as elevating lysozyme activity (Zhou et al, ), hydrolase enzyme activity (Li et al, ) and respiratory burst activity (Lu et al, ). The antioxidation and immune response of vitamin E has been observed in many aquatic animals, especially in fish, such as largemouth bass, Micropterus salmoides (Li, Lian, Chen, Wang, & Sang, ), yellow catfish, Pelteobagrus fulvidraco (Lu et al, ) and grass carp, Ctenopharyngodon idellus (Li et al, ). However, few studies have been done on crustaceans.…”
Section: Introductionmentioning
confidence: 99%
“…A summary on the vitamin E requirements of fish indicated that the levels vary from 25 to 200 mg vitamin E/kg of the diet (NRC, ). For example, the vitamin E requirement for largemouth bass ( Micropterus salmoides ; Li, Lian, Chen, Wang, & Sang, ), red drum ( Sciaenopsocellatus ; Peng & Gatlin, ), Atlantic salmon ( Salmo salar ; Hamre & Lie, ), mrigal ( Cirrhinusmrigala ; Paul, Sarkar, & Mohanty, ), rohu ( Labeorohita ; Sau, Paul, Mohanta, & Mohanty, ) and black sea bream ( Acanthopagrusschlegeli ; Peng et al, ) was 73–108, 31, 60, 99, 131.91 and 150 mg/kg, respectively.…”
Section: Introductionmentioning
confidence: 99%